Sustainability disclosure: Impact of its extent and quality on value of listed firms in Nigeria - N. G. Nwaigwe; G. N. Ofoegbu; N. O. Dibia; C. V. Nwaogwugwu (Cogent Business & Management, 2022)
Aside from scanty research in developing economies' context on the sustainability and firm value nexus and the dearth of studies on disclosure quality globally, available studies seem to have neglected the multidimensional nature of disclosure quality in measuring the construct. This paper was, therefore, designed to examine the effect of the extent and quality of sustainability disclosure on market value of firms. To achieve the study's objectives, 31 relevant sustainability performance indicator aspects were analyzed for the 39 companies drawn from 9 sectors for the period 2010-2019. This results in 390 firm-year observations and 12,090 data points used to calculate unweighted sustainability extent and quality indices. Findings from regression analysis suggest a positive non-significant association between extent of sustainability disclosure and firm market value. Quality of sustainability disclosure was found to be negatively related to market value. Variations were also found in the value effect of the extent and quality of sustainability disclosure across the economic, social and environmental dimensions of sustainability. Joining two separate streams of research-extent and quality of sustainability disclosure-the study offers new and insightful evidence on the value relevance of the duo from a developing clime. This result is relevant for firm managers who make decisions about sustainability initiatives knowing that investors react to the reportage of these initiatives. It is also of relevance in the implementation of robust policies that encourage joint efforts by firms and the investing public in fostering even sustainable development.
Keywords: 650; extent of disclosure; Firm market value; quality of disclosure; sustainability disclosure